The effect of Verotoxin Producing Escherichia coli in Development of Experimental Gastroenteritis among Streptomycin Treated Murine Model: A Longitudinal Study - Mosharraf, Fahareen Binta; Ahsan, Chowdhury Rafiqul; Nessa, Jamalun; Yasmin, Mahmuda (Bangladesh Journal of Microbiology, 2016)
Escherichia coli O157:H7 is a newly emerged pathogen, which has been recognized as a major cause of large scale epidemics and thousands of sporadic cases of gastrointestinal illness. This observation particularly calls for the in vivo examination of E. coli O157 candidates in an attempt to mimic various aspects of E. coli O157:H7 disease symptoms in humans. Healthy conventional Swiss albino mice were used for investigating the clinical manifestation exerted by stx1A and stx2A positive E. coli O157:H7 in various doses applied through three alternative routes (oral, intramuscular and intraperitoneal). The highest titer of orally added E. coli 0157:H7 (109 CFU ml-1) among the five test doses had started symptoms at the earliest time and manifested most of the classical symptoms. The symptoms started to become visible at 14th hour, increased with time and had reached moribund condition near 48th hour just before death of the host. The oral way of E. coli O157:H7 addition at the dose of 100 ?l suspension containing 1 X 109CFU ml-1 was taken as the most potent concentration in producing bacterial fatality and hence was selected as the Minimum Lethal Dose (MLD). Bangladesh J Microbiol, Volume 30, Number 1-2,June-Dec 2013, pp 31-38